Analysis of the Influence of Food Prices on Inflation in Sumenep Regency in 2020-2023 - Najib, Nanda Muhammad; Zuhri, Nabila Sinta; Romadhoni, Sri (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
Food prices are one of the main factors that influence inflation. An increase in food prices can have a significant impact on inflation, especially in developing countries like Indonesia. This research aims to see the influence of food prices such as rice, eggs, chicken meat, oil, shallots, LPG gas, urea fertilizer on inflation in Sumenep Regency. The method chosen in this research is a quantitative method using time series data regression analysis techniques from the period January 2020 to December 2023. The results of this research show that the prices of rice and LPG gas have a negative influence on inflation, while the prices of chicken meat, oil and onions red, and urea fertilizer has a positive influence. Meanwhile, eggs have no effect on the inflation rate in Sumenep Regency